Academic Writing in Russia: The Urge for Interdisciplinary Studies - I. B. Korotkina (Высшее образование в России, 2018)
Debates over academic writing as a new discipline, or rather trend, started in the journal seven years ago and initially involved academics from different fields. However, when the focus shifted towards teaching writing in English, the discussion narrowed and lost its urge. The analysis of the first papers shows that the importance of developing academic writing skills is understood by the Russian academic community, but most academics have limited awareness of academic writing as a discipline and field of research aimed at solving major problems in education and science. The paper focuses on the theoretical and methodological issues of academic writing and gives a brief overview of how it emerged into a well-developed discipline in Western, mostly US, universities. To achieve the goal of introducing academic writing into the higher education, Russian academics need to collaborate and get involved into multilateral action and interdisciplinary research. The paper concludes that disciplinary divides can be overcome through developing theoretical and conceptual issues of academic writing as rhetoric and composition studies.